2020
DOI: 10.36849/jdd.2020.4546
|View full text |Cite
|
Sign up to set email alerts
|

MRI Assessment of Arm and Calf Muscle Toning With High-Intensity Focused Electromagnetic Technology: Case Study

Abstract: Arms and calves have long been a subject of interest in aesthetic medicine. Current surgical and non-invasive procedures focus on sagging skin and fat deposits without targeting the muscles. The aim of this study is to investigate the feasibility of high-intensity focused electromagnetic (HIFEM) technology for arm and calf toning through simultaneous fat reduction and muscle strengthening. In this case study, two subjects received four 20-minute HIFEM treatments of biceps, triceps, and calves, with the outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 8 publications
1
34
0
Order By: Relevance
“…2 HIFEM procedure that is based on the principles of electromagnetic induction was found to be an effective body shaping modality for multiple body parts. [13][14][15] HIFEM selectively and noninvasively stimulates the striated muscle tissue by utilizing supramaximal contractions performed with higher tension than those achieved during regular exercise. Besides the muscle enlargement due to the muscle fiber hypertrophy and hyperplasia, 16 various imaging techniques including CT, 17 MRI, 14 and diagnostic ultrasound 18 documented SAT-reducing effect of HIFEM when applied to the abdomen.…”
Section: Introductionmentioning
confidence: 99%
“…2 HIFEM procedure that is based on the principles of electromagnetic induction was found to be an effective body shaping modality for multiple body parts. [13][14][15] HIFEM selectively and noninvasively stimulates the striated muscle tissue by utilizing supramaximal contractions performed with higher tension than those achieved during regular exercise. Besides the muscle enlargement due to the muscle fiber hypertrophy and hyperplasia, 16 various imaging techniques including CT, 17 MRI, 14 and diagnostic ultrasound 18 documented SAT-reducing effect of HIFEM when applied to the abdomen.…”
Section: Introductionmentioning
confidence: 99%
“…Published studies investigating the effect of HIFEM on buttocks 36,37 did not yet present any quantitative data, but did show high patient satisfaction and pronounced buttock lifting effect contributing to esthetic improvement in the buttock appearance seen in digital photographs. In regard to arms and calves, a case study has been published by Katz et al 38 The study used MRI imaging and found a 17.1% increase in biceps muscle mass, 10.2% in triceps muscle mass, and 14.6% in gastrocnemius muscle mass accompanied by a significant reduction in arm and calf fat thickness (see Figure 2 for an example of HIFEM effect on arms).…”
Section: Expected Resultsmentioning
confidence: 99%
“…The magnetic stimulation-induced muscle hypertrophy, fat reduction and reduction in abdominal separation has been observed in several studies [27][28][29]. Kent et al [30], who investigated the effects of high-intensity focused electromagnetic technology for the induction of changes in abdominal muscles and abdominal subcutaneous fat, showed a significant patient subcutaneous fat reduction and the simultaneous thickening of the rectus abdominis muscle without reporting any sign of pain or discomfort.…”
Section: Discussionmentioning
confidence: 99%